The Influence of Pregnancy on the Recurrence of Cutaneous Malignant Melanoma in Women - M. Albersen; V. I. Westerling; P. A. M. van Leeuwen (Hindawi Limited, 2010)
Objective. The aim of this study was to determine whether pregnancy increases the recurrence risk of cutaneous malignant melanoma (CMM) in women with a history of stage I CMM. Methods. The electronic medical databases of Medline and Embase were explored. All 1084 obtained articles were screened on title and abstract using predetermined inclusion and exclusion criteria. A critical appraisal of relevance and validity was conducted on the remaining full text available articles. Results. Two studies were selected. Both studies revealed no significant difference in disease-free survival between women with stage I CMM and the control population. Conclusion. Pregnancy does not increase the recurrence risk of CMM in women with a history of stage I CMM.